AGROPINE 2011 Meeting conclusions - Mutke S.; Piqué M.; Calama R. (Mediterranean stone pine for agroforestry, 2013)
The future of Mediterranean Stone Pine requires an effective commercial distinction from other pine seeds and a stable, increased production from agroforestry systems.
AGROPINE 2011 International Meeting on Mediterranean Stone Pine for Agroforestery, 2011/11/17-19, Valladolid (Spain)